PEMBENTUKAN KERANGKA HUKUM INTERNASIONAL BAGI PENCEGAHAN PERDAGANGAN KAYU ILEGAL - Aktieva Tri Tjitrawati (Yuridika, 2012)
The implementation of international trade in the forest products that related with sustainable production and consumption cycle process include the legal regime of international trade in natural resources, the State Government exporters and importers, as well as markets in importing countries. International trade law regime is still have a weak role in preventing the illegal logging trade, hence it is required a International Law drafting concepts which can avoid illegal actions by obligating the exporters or the exporter countries with certain obligations. These efforts require a reconceptualization the relationship between trade and environment, which until now are often placed in the same dichotomy.